On The Dysfunctional Consequences of Salesperson Exhaustion. Issue 2 (2nd April 2016) - Darrat, Mahmoud; Atinc, Guclu; Babin, Barry J.
Abstract : Salespeople are particularly susceptible to stress given the nature of their roles. This research examines emotional exhaustion as a facilitator of dysfunctional sales behaviors and accentuates the importance of leadership processes in mitigating stress. Results indicate that leader member exchange is sequentially related to emotional exhaustion, salesperson deviance (organizational, frontline), and turnover intentions. Managerial implications are discussed along with suggestions for enhancing salesperson-manager relationships and mitigating salesperson deviance.